The next generation of laser spectroscopy experiments using light muonic atoms. (November 2018) - Schmidt, S; Willig, M; Haack, J; Horn, R; Adamczak, A; Ahmed, M Abdou; Amaro, F D; Amaro, P; Biraben, F; Carvalho, P; Chen, T-L; Fernandes, L M P; et al.
Abstract: Precision spectroscopy of light muonic atoms provides unique information about the atomic and nuclear structure of these systems and thus represents a way to access fundamental interactions, properties and constants. One application comprises the determination of absolute nuclear charge radii with unprecedented accuracy from measurements of the 2S - 2P Lamb shift. Here, we review recent results of nuclear charge radii extracted from muonic hydrogen and helium spectroscopy and present experiment proposals to access light muonic atoms with Z ≥ 3. In addition, our approaches towards a precise measurement of the Zemach radii in muonic hydrogen ( μ p) and helium ( μ 3 He + ) are discussed. These results will provide new tests of bound-state quantum-electrodynamics in hydrogen-like systems and can be used as benchmarks for nuclear structure theories.